Replica plating of Coprinus cinereus colonies using asexual spores - E. Polak; U. Kües; M. Aebi (Fungal Genetics Reports, 1997)
Asexual spores (oidia) of Coprinus cinereus adhere to surfaces such as metal or velveteen. We used this feature to develop a new method for replica plating and demonstrate its value in screening for auxotrophic mutants and mutants in sporulation.